Recognizing and managing myocarditis following COVID-19 vaccination: mitigating risk of sudden cardiac death in athletes - Kauth, M.; Kovacs, R. J. (Journal of the American College of Cardiology, 2022)
Background: Myocarditis is a risk for sudden cardiac death (SCD) in athletes, and its recognition and appropriate management are of paramount importance for safe return to athletic activity. Myocarditis has been reported as a complication of the mRNA COVID-19 vaccines, especially in young males. It is not known whether prior COVID-19 infection increases risk for myocarditis after vaccination. We present a case of a young athletic male previously infected with COVID-19, who developed myocarditis after a second dose of the Pfizer mRNA COVID-19 vaccine. Case: A 19-year-old healthy male presented to the ED. He described anterior squeezing chest pain without association with activity or rest, and lateral chest pain exacerbated by movement. 6-8 months prior, he tested positive for COVID-19 infection via RT-PCR saliva test with symptoms that included rhinorrhea, cough, anosmia, ageusia, and mild chest pain. Symptoms resolved spontaneously. He later received two doses of the Pfizer vaccine, with second dose given 10 days prior to presentation. Vital signs and physical exam were normal. ECG showed 0.5-1mm ST segment elevation in the inferior and lateral leads. Troponin-I was elevated and peaked at 3.61 ng/mL, CBC, comprehensive metabolic panel, TSH, and C-reactive protein were normal. CT angiogram of the chest was normal. Transthoracic echocardiogram demonstrated normal left ventricular systolic function, normal wall motion, and no pericardial effusion. Decision-making: This patient was clinically diagnosed with myocarditis. He was treated with ibuprofen and beta blocker with improvement. Cardiac magnetic resonance imaging with and without gadolinium demonstrated minimal T2 signal elevation, but did reveal late gadolinium enhancement of 25-75% of the inferior and lateral walls. Athletic activity was restricted for 3-6 months and follow-up testing is yet to be completed. Conclusion: Although rare, myocarditis is a recognized complication following COVID-19 mRNA vaccination. Risk may be increased in younger male patients, and those previously infected with COVID-19. It is important to anticipate this complication of vaccination in the competitive athlete population, to mitigate risk of SCD.